Primary cutaneous plasmablastic lymphoma revealing clinically unsuspected HIV infection - Silvio Alencar Marques; Luciana P. Fernandes Abbade; Marcelo Massaki Guiotoku; Mariangela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Plasmablastic lymphoma is a rare subtype of diffuse large B-cell lymphoma more frequently diagnosed in immunosuppressed patients, mainly HIV-infected. Primary cutaneous plasmablastic lymphoma is extremely rare, and in this patient it was the first clinical manifestation of unsuspected HIV-infection.